2018
DOI: 10.1002/pds.4560
|View full text |Cite
|
Sign up to set email alerts
|

Association between dipeptidyl peptidase‐4 inhibitors and urinary tract infection in elderly patients: A retrospective cohort study

Abstract: The long-term use of DPP-4 inhibitors by elderly patients, particularly male patients with prostatic hyperplasia, may increase the risk of UTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Symptomatic hypoglycemia, pancreatitis (acute or chronic), skin disorders of non-extrinsic origin, severe infections, and cancer were collected as major AEs. [18][19][20][21][22] Microvascular and macrovascular complications were also collected. AE terms were referred to MedDRA V. 15 Clinical care/Education/Nutrition included the levels of hemoglobin A1c (HbA1c), fasting blood glucose, fasting insulin, and urinary albumin.…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic hypoglycemia, pancreatitis (acute or chronic), skin disorders of non-extrinsic origin, severe infections, and cancer were collected as major AEs. [18][19][20][21][22] Microvascular and macrovascular complications were also collected. AE terms were referred to MedDRA V. 15 Clinical care/Education/Nutrition included the levels of hemoglobin A1c (HbA1c), fasting blood glucose, fasting insulin, and urinary albumin.…”
Section: Discussionmentioning
confidence: 99%
“…Even though UTI is not a known adverse effect of DPP4i, there is a single study that reported an increased risk of UTI with the use of DPP4i when compared with sulfonylureas. 28 We also observed inverse associations between SGLT2is and anemias (D64). Meta-analyses of RCTs found that SGLT2i use increased hemoglobin levels in patients with diabetes and chronic kidney disease.…”
Section: Discussionmentioning
confidence: 57%
“…We cannot exclude the possibility that the lower rate of UTI hospitalization among SGLT2i users was due to adverse events following DPP4i use. Even though UTI is not a known adverse effect of DPP4i, there is a single study that reported an increased risk of UTI with the use of DPP4i when compared with sulfonylureas 28 …”
Section: Discussionmentioning
confidence: 99%
“…Sodium-glucose cotransporter 2 (SGLT2) mediates approximately 80–90% of renal glucose reabsorption under normal physiologic conditions, and SGLT2i can reduce 30–50% of the filtered glucose load in T2DM patients by increasing urinary glucose excretion [ 41 ]. However, the Food and Drug Administration (FDA) issued safety warnings for UTIs which may represent a leading cause of sepsis and are potentially life-threatening [ 42 , 43 ]. We conducted a meta-analysis to evaluate the benefit on the cardiovascular system and the potential risk of infection of SGLT2i in T2DM patients compared to metformin.…”
Section: Discussionmentioning
confidence: 99%